Universidade Federal do Ceará - Agente redistribuidor ou concentrador de renda ? - Guimarães, Maria Teresa Albuquerque (1982)
The problem analysed in this study is concerned with the topic: education and income inequality. The evolution of the question in tyhe history of economic thought goes bacl tp Adam Smith, David Ricardo, Alfred Marshall and Karl Marx. Modernly, a new line of thought in economics was development trying to demonstrate that education is a determining fator in economic devlopment and that a change in human capital distribution would reduce income inequalities existing among the various social strata of the population. This is the basic conceptions of the so called Hman Capital Theory. It is obvious that one cannot make education the only responsible for solving the socio-economic problems of the people, mainly when one id concerned with a social formation of a dependent capitalist economy, as in the case of Brazil. In this country much emphasis has been given to the question of democratization of educational opportunities, at least, at the planning level in the Federal Government, in the sense of leading toward a reduction of social inequalities. In which sense this democratization fo educational oportunities is taking place at the Federal University of Ceará ? The results of this study show that this University is working, continuously, as another agent which reinforces the income concentration tendency in its course of action and that the youngsters originating from high-income families usually choose those courses whith guarantee a higher social status.